Seeing Double: Exploring the Phenomenology of Self-Reported Absence of Rivalry in Bistable Pictures - Filevich, Elisa; Becker, Maxi; Wu, Yuan-hao; Kühn, Simone (Frontiers in Human Neuroscience, 2017)
Ambiguous images such as Rubin’s vase-face can be interpreted in at least two different ways. These interpretations are typically taken to be mutually exclusive, and ambiguous images have thus served as models of perceptual competition. Here, we present data that challenges this view. In an online survey, we found that a large proportion of people within the general population reported that the two percepts were not competing but could be perceived simultaneously. Of those who reported that they could see both percepts simultaneously, we invited 17 participants to take part in a functional magnetic imaging (fMRI) experiment. In the scanner, participants saw images that could be interpreted as either a landscape or a face and reported at every point in time whether they perceived predominantly the face, the landscape, or both simultaneously. We explored behavioural and neurophysiological (with functional magnetic resonance imaging, fMRI) correlates of the reported subjective experience of entertaining two percepts simultaneously by comparing them to those of the simple percepts (i.e., face or landscape). First, by comparing percept durations, we found that the simultaneous state was as stable as the two other percepts. Second, by measuring blood-oxygen-level-dependent (BOLD) signal levels within the fusiform face area (FFA), occipital face area (OFA), and parahippocampal place area (PPA), we found evidence from objective data that confirmed the subjective reports. While the results in FFA and OFA were not conclusive, in PPA, BOLD signal levels during subjective reports of perceiving both a landscape and a face were lower than the BOLD signal levels associated with reports of perceiving a landscape. (And, in turn, reports of seeing a landscape were associated with greater BOLD signal levels than reports of seeing a face, thus suggesting that BOLD signal levels in PPA are a valid correlate of subjective experience in this task). In sum, the objective measures suggest that entertaining two percepts simultaneously in mind can be regarded as a distinct (mixed) perceptual state. We argue with these results that a more central role of subjective report in cognitive neuroscience is sometimes warranted.